Growth performance and economics of feeding Soymilk in Murrah buffalo calves: Soymilk feeding in Murrah buffalo calves - Mohammed Ishan Hashmi; Dipin Chander Yadav; Narender Singh; Devender Singh Bidhan; vishal sharma; Amandeep; Umesh kumar jaiswal; Rohit sharma (Indian Journal of Dairy Science, 2024)
This research was designed to evaluate the effect of Soymilk on growth and economics of feeding in Murrah buffalo calves. The buffalo calves were randomly divided into three treatment groups. Whole milk/dam’s milk fed experimental calves were taken in control group. The experimental groups consist of Whole milk and Soymilk in 75:25 and 50:50 ratio. Standard feeding and management practices were followed throughout the experimental period. To assess the efficacy of Soymilk feeding on the growth performance, body weight and body measurements (body height, heart girth, abdominal girth and body length) were recorded at the start of the experiment and thereafter at 15 days interval. The results of the study indicated that body weight parameters (average body weight, body weight gain, cumulative body weight gain and average daily body weight gain) and body measurements parameters (body height, cumulative body height, heart girth, cumulative heart girth, abdominal girth and cumulative body length) did not differ significantly among the control group and Soymilk fed treatment groups. The economics of feeding calculated at the end of experiment revealed that net profit in total feeding cost/kg weight gain was Rs. 106.92 and 130.35 for 25 percent and 50 percent Soymilk replacement group, respectively. Through this experimentation, it can be concluded that Soymilk has similar effect on growth performance of calves as Whole milk and more economical than whole milk feeding, therefore Soymilk may possibly replace whole milk up to 50 percent level.